Effect of caffeine on cycling time-trial performance in the heat - Pitchford, N. W.; Fell, J. W.; Leveritt, M. D.; Desbrow, B.; Shing, C. M. (Journal of Science and Medicine in Sport, 2014)
Objectives: The purpose of this investigation was to determine whether a moderate dose of caffeine would improve a laboratory simulated cycling time-trial in the heat. Methods: Nine well-trained male subjects (VO2max 64.4 ± 6.8 mL min-1 kg-1, peak power output 378 ± 40 W) completed one familiarisation and two experimental laboratory simulated cycling time-trials in environmental conditions of 35 °C and 25% RH 90 min after consuming either caffeine (3 mg kg-1 BW) or placebo, in a double blind, cross-over study. Results: Time-trial performance was faster in the caffeine trial compared with the placebo trial (mean ± SD, 3806 ± 359 s versus 4079 ± 333 s, p = 0.06, 90%CI 42-500 s, 86% likelihood of benefit, d = -0.79). Caffeine ingestion was associated with small to moderate increases in average heart rate (p = 0.178, d = 0.39), VO2 (p = 0.154, d = 0.45), respiratory exchange ratio (p = 0.292, d = 0.35) and core temperature (p = 0.616, d = 0.22) when compared to placebo, however, these were not statistically significant. Average RPE during the caffeine supplemented time-trial was not significantly different from placebo (p = 0.41, d = -0.13). Conclusion: Caffeine supplementation at 3 mg kg-1 BW resulted in a worthwhile improvement in cycling time-trial performance in the heat. Design: Double-blind cross-over study.